Modulation of statin-activated shedding of Alzheimer APP ectodomain by ROCK. - Steve Pedrini; Troy L Carter; George Prendergast; Suzana Petanceska; Michelle E Ehrlich; Sam Gandy (PLoS Medicine)
Background Statins are widely used cholesterol-lowering drugs that act by inhibiting HMGCoA reductase, the rate-limiting enzyme in cholesterol biosynthesis. Recent evidence suggests that statin use may be associated with a decreased risk for Alzheimer disease, although the mechanisms underlying this apparent risk reduction are poorly understood. One popular hypothesis for statin action is related to the drugs' ability to activate alpha-secretase-type shedding of the alpha-secretase-cleaved soluble Alzheimer amyloid precursor protein ectodomain (sAPP(alpha)). Statins also inhibit the isoprenoid pathway, thereby modulating the activities of the Rho family of small GTPases-Rho A, B, and C-as well as the activities of Rac and cdc42. Rho proteins, in turn, exert many of their effects via Rho-associated protein kinases (ROCKs). Several cell-surface molecules are substrates for activated alpha-secretase-type ectodomain shedding, and regulation of shedding typically occurs via activation of protein kinase C or extracellular-signal-regulated protein kinases, or via inactivation of protein phosphatase 1 or 2A. However, the possibility that these enzymes play a role in statin-stimulated shedding has been excluded, leading us to investigate whether the Rho/ROCK1 protein phosphorylation pathway might be involved. Methods and findings We found that both atorvastatin and simvastatin stimulated sAPP(alpha) shedding from a neuroblastoma cell line via a subcellular mechanism apparently located upstream of endocytosis. A farnesyl transferase inhibitor also increased sAPP(alpha) shedding, as did a dominant negative form of ROCK1. Most conclusively, a constitutively active ROCK1 molecule inhibited statin-stimulated sAPP(alpha) shedding. Conclusion Together, these data suggest that statins exert their effects on shedding of sAPP(alpha) from cultured cells, at least in part, by modulation of the isoprenoid pathway and ROCK1.